PENENTUAN MASA TANAM KEDELAI BERDASARKAN ANALISIS NERACA AIR DI KABUPATEN KONAWE SELATAN, SULAWESI TENGGARA - Musyadik Musyadik; Agus salim; Tri Marsetyowati (Widyariset, 2014)
South Konawe is a regency in Southeast Sulawesi which is dominated by dry land around 42,151 ha. Out of this area, only 2,100 ha was utilized for soybean planting with yield of 1.051 t/ha. One of problems for this low productivity is not optimal use of the technology in terms of usage time of planting. From the analysis of the water balance sheet, it shows that the surplus occurs in January, March, April, May, June, and July. However, soybean can only be planted in May because it meets the water requirement for soybean that is 250–300 mm/month. On the other hand, deficit months occur in February, August–December.